Oil palm (Elaeis guineensis) seed characteristics and germination potential as influenced by maturity stage and fruitlet position on a bunch - Ghazali, Mohd Norsazwan; Sinniah, Uma Rani; Namasivayam, Parameswari (Malaysian Palm Oil Board, 2024)
Oil palm is mainly propagated through dura × pisifera hybrid (DxP) seeds. In the natural environment, oil palm seeds require more than eight months of storage to achieve 25% germination due to a combination of morphological and physiological dormancy. Therefore, improvement in terms of the percentage of germination, uniformity and reduction in time to germination will benefit seed producers tremendously. In this study, the effect of harvesting at three maturity stages (18, 20 and 22 weeks after pollination or WAP) and six seed positions within a bunch (Proximal-Base, Proximal-Apex, Middle-Base, Middle-Apex, Distal-Apex and Distal-Base) on seed characteristics and germination potential were evaluated in a split-plot design. Seeds harvested at 20 WAP had 80% black-coloured seeds with the highest germination of 85.1%, compared with 70.5% and 80.9% at 18 and 22 WAP, respectively. Increasing seed maturity from 18 to 20 WAP showed more seeds shifting from semi-white and white to black (up to 40% more). Seeds located at the base region of the spikelet were smaller in size and were predominantly white with no differences in germination capacity.